Medición de los aportes de la gestión estratégica de comunicación interna a los objetivos de la organización (2011)
Strategic management of in-house communication (SMIC) has been transformed into a vector of fundamental competitiveness in new organizational scenarios, but the media professionals who appreciate the contribution of this action are few and far between. This study was designed to determine how the specific objectives of SMIC can be tied in to the general objectives of the organization. The fundamental logic of management was reviewed (total quality control, six sigma, added value, benchmarking, zero base budget and comprehensive management chart) along with its tendencies in measurement. The methods and tools used in a series of successful cases to measure SMIC were examined as well. The result was a relational matrix showing new schemes for understanding the contribution of communications to an organization.